(untitled) (AL MUNAZHZHARAH, 2018)
Marriage is a spiritual bond between a man and woman as husband and wife with the aim of forming a happy home. However, marriage will be an interesting issue when marriages are held at an age that is not supposed to or does not meet the age determined by the Marriage Law in Indonesia. As a form of answer for the focus of research, researchers use qualitative research. After conducting research the researcher can conclude that the impact of early marriage is divided into two parts, namely the positive impact and negative impact. (a) the positive impact of marriage at an early age can prevent the habits of young people in the era of globalization as it is now before heading to marriage, which is in terms of the current trend of young people, and avoid adultery. (b) The negative impact is that divorce is easy, children’s education becomes neglected, socio-economic conditions become broken and messy and can also cause divisions towards family relationships.